A multi-layer resin film infusion process to control CNTs distribution and alignment for improving CFRP interlaminar fracture toughness. (15th March 2021) - He, Yonglyu; Zhang, Jianwei; Yao, Liaojun; Tang, Jun; Che, Bixuan; Ju, Su; Jiang, Dazhi
Abstract: The excellent mechanical properties of carbon nanotubes (CNTs) have not been fully demonstrated in toughening laminated composites. One important reason is that the distribution and orientation of the CNTs in composites processing are not well controlled. In this study, 2D fluid–structure interaction simulation was conducted to explore the feasibility of controlling the alignment and distribution of CNTs by using guided resin flow. A multi-layer resin film infusion (MLRFI) process was developed to achieve controlled CNTs distribution and orientation in the composites. The composite laminates with 0.1 wt.% MWCNTs prepared by the MLRFI method demonstrated a 53.6% improvement in initial crack propagation GIC, and 78.9% increase in GIC at the steady state, compared to the baseline composite. Based on the microscopic examinations on fracture surface and the determination of crack propagation R-curve using the Foote's theory, the significant improvement in the fracture toughness was attributed to the toughening effects of CNTs. Particularly, the addition of CNTs can toughen the epoxy and promote more fibre bridging during crack propagation.